Assessing the willingness to pay of fishermen, Biologists and Engineers tor Sustainable Management of Thondamanaaru Lagoon in Jaffna District Sri Lanka - Sooriyakumar, K.; Sivashankar, S.; Sarujan, S.; Nithila, K.; Kiriyaliny, V.; Selvana, S.; Anushiya, S. (International Lake Environment Committee Foundation, 2025)
As one of the prominent lagoons in northern Sri Lanka, the Thondamanaru lagoon provides a wide range of ecosystem services that are highly valued by society. However, the state intervention of barrage closure to prevent the salinity issues in the groundwater of the region has posed serious challenges on the biodiversity of the Thondamanaaru lagoon as well as the livelihoods of artisanal fishermen living in this area. The situation raises concerns not only among the local people but also among all the stakeholders related to this lagoon ecosystem management such as, biologists, engineers, fishermen. Therefore, this study aims to understand the preferences and willingness to pay of fishermen, biologists, and engineers using a choice experiment approach to support sustainable lagoon management. The attributes considered for this study include the levels of barrage operation, fish stocks, mangroves, tourist facilities, and payments. A total of 180 fishermen, 150 engineers, and 154 biologists were randomly selected for this study, and the preferences of different stakeholders were analyzed using a mixed logit model. The results show the preference order of barrage operation of fishermen and biologists as follows: complete opening of sluice gate throughout the year, opening for one month per year and complete closure of sluice gate, but the preference order of barrage operation of engineers is as follows: complete closure of sluice gate, opening for one month per year and complete opening of sluice gate throughout the year. However, all stakeholders are willing to pay to open the sluice gate for one month per year. Biologists had the highest WTP (LKR 2956.65) for sluice gate opening for one month per year. In contrast, engineers prefer to completely close the barrage and open the barrage one month per year levels than completely open the barrage. Notably, fishermen, biologist, and engineers are willing to pay for an increase in fish stock, mangroves, and improvements in tourism. Furthermore, the findings revealed that fishermen above 50 years of age were more willing to accept compensation for the complete closure of the sluice gate per month compared to those below 50 years of age. Further, engineers’ income and their knowledge regarding the lagoon significantly influence their choice, while biologists’ gender, knowledge, and understanding of lagoon management practices significantly influence their choice. These findings could be useful to policymakers to develop appropriate policy to maximize the welfare to society from lagoon and sustainable ecosystem management.